(untitled) (Asian Journal of Agriculture, 2025)
Abstract. Lugundi HS, Maleko DD, Kizima JB, Nziku ZC, French P, Urassa V, Mangesho W, Gooddluck S, Lugeye S, Mgonja H, Mngulu S, Selemani IS. 2025. Influence of fertilization and defoliation interval on forage yield and chemical composition of Cenchrus ciliaris under sandy soil. Asian J Agric 9: 234-243. Improper defoliation intervals and nutrient-deficient soil limit the yield and quality of forages, resulting in poor dairy production. Using inorganic fertilizers to improve soil nutrition is expensive and pollutes the environment. The study was conducted to assess the influence of organic fertilization and defoliation intervals on the yield and chemical composition of Cenchrus ciliaris L. during the rainy season. The study was designed as a 3 × 4 factorial arrangement in a Completely Randomized Design (CRD), a method that allows for a comprehensive analysis of multiple factors and their interactions. It included three cutting intervals (9, 16, and 23 days) and three fertilizer types (compost cow manure, green processed bioorganic fertilizer, and liquid processed bioorganic fertilizer), plus a control with four replications. The study revealed that all fertilizer types had a significant influence on biomass yield, metabolizable energy, and crude protein percentages. In addition, fertilizer applications significantly decreased NDF, ADF, and ADL. On the other hand, the results show that the longer the cutting interval, the higher the biomass yields, but lower protein content and metabolizable energy. Cenchrus ciliaris fertilized compost cow manure and cut at a 23-day interval had a higher biomass yield and reasonable nutritive value. The study suggests the importance of considering fertilization and a cutting interval as appropriate management practices for C. ciliaris in related soil types and climates.